Fiscal Consolidation Start and its Determinants Analysis Within European Member Countries - Lucia Mihóková (Montenegrin Journal of Economics, 2017)
Purpose: The purpose of the research from the theoretical point of view is to define the "start of fiscal consolidation" and to clarify the effects of selected determinants on its initiation. The purpose of the paper, in an empirical context, is to empirically assess the impact of selected determinants on the start of consolidation in the EU member states in 1995-2015 using quantitative economics. The paper was developed within the project VEGA 1/0967/15. Methodology: The empirical assessment of the research objective is divided into four phases: (1) creation of research review using EBHC methodology, (2) identification of “start” of fiscal consolidation within selected period, (3) panel econometric analysis: model specification, quantification of model’s parameters and model verification and (4) research assessment and discussion. Within the analysis, the traditional, specific and general methods were used (systemic review according to EBHC methodology, content analysis, panel regression analysis, synthesis). Approach: Approach identifies “start” of consolidation episodes using selected identification rules. Using the panel regression analysis (OLS, FEM and REM models) approach the statistically significant macroeconomic, fiscal, political and other determinants and quantification of the polarity of their impact on the fiscal consolidation start were analysed. Findings: Based on the performed econometric analysis can be stated that the start of consolidation is significantly determined by initial macroeconomic and fiscal situation in the country which are captured by the size of output gap and GDP growth as well as the size of CAPB, budget expenditure and the revenue side. Political and other determinants (such as crisis) can also influence the start of consolidation episodes..